Aplikasi Molecularly Imprinted Polymer untuk Bioanalisis Senyawa Obat: Application of Molecularly Imprinted Polymers for Bioanalysis of Drug Molecules - Untung Gunawan; Dion Notario; Shakira Aprillia Tanudjaja; Patrick Renata; Feronia Reni Cyrena Santoso; Atthar Luqman Ivansyah (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2025)
Determination of drug concentration in biological specimens, including blood, plasma, serum, urine, tissue, and feces is a critical aspect of bioanalysis. The increasing interest in research on drug molecules, both existing drugs and their metabolites, and new drug candidates shows that a new development approach is needed for their bioanalytical methods. Sample preparation is an important step to eliminate the influence of the matrix and improve the analytical performance of a method. Molecularly imprinted polymer (MIP) as a separation method with unique features that are selective to target molecules has been applied to various applications and benefits, especially when used as an adsorbent in preparation methods for the analysis of complex biological matrices. The purpose of this study was to provide an overview of the use of MIP in the bioanalysis of drug compounds. The method used in this study uses a review of articles related to the concept of bioanalysis and the application of MIP for the analysis of drug components in biological matrices. Based on the results of the study, there has been an increase in the number of studies on the development of MIP over the last decade. Investigations show satisfactory results in MIP-based bioanalysis methods. The results of the study show the superiority of MIP as a preparation method that has high accuracy, reproducibility, sensitivity, speed, and cost-effectiveness, which makes it suitable for clinical use. This study can be a preliminary for further research on the development of MIP for bioanalysis of drug molecules. Keywords: Bioanalysis; Biological matrices; Sample preparation; Molecularly imprinted polymer.